A rare missense variant of CASP7 is associated with familial late‐onset Alzheimer's disease. Issue 3 (29th November 2018) - Zhang, Xiaoling; Zhu, Congcong; Beecham, Gary; Vardarajan, Badri N.; Ma, Yiyi; Lancour, Daniel; Farrell, John J.; Chung, Jaeyoon; Mayeux, Richard; Haines, Jonathan; Schellenberg, Gerard; et al.
Abstract: Introduction: The genetic architecture of Alzheimer's disease (AD) is only partially understood. Methods: We conducted an association study for AD using whole sequence data from 507 genetically enriched AD cases (i.e., cases having close relatives affected by AD) and 4917 cognitively healthy controls of European ancestry (EA) and 172 enriched cases and 179 controls of Caribbean Hispanic ancestry. Confirmation of top findings from stage 1 was sought in two family‐based genome‐wide association study data sets and in a whole genome–sequencing data set comprising members from 42 EA and 115 Caribbean Hispanic families. Results: We identified associations in EAs with variants in 12 novel loci. The most robust finding is a rare CASP7 missense variant (rs116437863; P  = 2.44 × 10 −10 ) which improved when combined with results from stage 2 data sets ( P  = 1.92 × 10 −10 ). Discussion: Our study demonstrated that an enriched case design can strengthen genetic signals, thus allowing detection of associations that would otherwise be missed in a traditional case‐control study.